The Leadership Concepts Of Peter G. Northouse Reflected In John Grisham’s Novel Character, Jake Brigance - Purnamasari, Linda (UNIVERSITAS PAKUAN, 2023)
The purpose of the research is to find the hero’s action that Jake Brigance does to the people in Canton based on the three novels of John Grisham, to find whether Jake has a good character based on Peter G. Northouse’s book “Leadership: Theory and Practice or not, to find that Jake Brigance’s character reflected the leadership character concepts in Peter G. Northouse’s book. find the theories of the leadership of Peter G. Northouse reflected in John Grisham’s novel character based on characteristics approach. The research is in a qualitative method, starting by collecting some data about the leadership concepts from Peter G. Northhouse titled The Leadership: Theory and Practice based on the characteristics approach. Then finding who is Jake Brigance, and why John Grisham puts him in the three of his novels (A Time to Kill, Sycamore Row, and A Time for Mercy) to be the main character and also can be a decision-maker of the problems in the novels. The aims of the research are to find the actions that Jake Brigance does to the people in Canton based on the three novels of John Grisham, to find whether Jake’s character is reflected in Peter G. Northouse’s book “Leadership:Theory and Practice or not.